Study of equilibrium carrier transfer in LaAlO3/SrTiO3 from an epitaxial La1−xSrxMnO3 ferromagnetic layer. (6th February 2018) - Telesio, F; Moroni, R; Pallecchi, I; Marré, D; Vinai, G; Panaccione, G; Torelli, P; Rusponi, S; Piamonteze, C; di Gennaro, E; Khare, A; Miletto Granozio, F; et al.
Abstract: Using x-ray magnetic circular dichroism and ab-initio calculations, we explore the La1− x Sr x MnO3 /LaAlO3 /SrTiO3 (001) heterostructure as a mean to induce transfer of spin polarized carriers from ferromagnetic La1− x Srx MnO3 layer into the 2DEG (two-dimensional electron gas) at the LaAlO3 /SrTiO3 interface. By out-of-plane transport measurements, the tunneling across the LaAlO3 barrier is also analyzed. Our results suggest small or vanishing spin-polarization for the 2DEG: magnetic dichroism does not reveal a neat signal on Ti atoms, while calculations predict, for the pristine stoichiometric interface, a small spin-resolved mobile charge of 2.5 × 10 13 cm −2 corresponding to a magnetic moment of 0.038 μ B per Ti atom, tightly confined within the single SrTiO3 layer adjacent to LaAlO3 . Such a small magnetization is hard to be detected experimentally and perhaps not robust enough to survive to structural disorder, native doping, or La1− x S r x MnO3 dead-layer effects. Our analysis suggests that, while some spin-diffusion cannot be completely ruled out, the use of ferromagnetic La1− x Sr x MnO3 epilayers grown on-top of LaAlO3 /SrTiO3 is not effective enough to induce robust spin-transport properties in the 2DEG. The examined heterostructure is nevertheless an excellent test-case to understand some fundamental aspects of the spin-polarized charge transfer in 2D wells.